2006
DOI: 10.1002/adma.200600634
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Organic Single‐Crystal Transistors on Flexible Substrates

Abstract: Flexible and conformable organic single crystals as thin as 150 nm are used for fabricating mechanically bendable organic single‐crystal field‐effect transistors on low‐cost plastic substrates (see figure and cover). We report effective field‐effect mobility as high as 4.6 cm2 V–1 s–1 for a flexible rubrene single‐crystal transistor, on/off ratio of ca. 106, threshold voltage of – 2.1 V, and a normalized subthreshold swing of 0.9 V nF decade–1 cm–2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
248
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(258 citation statements)
references
References 29 publications
6
248
0
4
Order By: Relevance
“…Within this effort, there are a few papers that perform tests of mechanical flexibility of organic devices and investigate the dependence of their performance on mechanical strain. For example, Briseno et al 4 developed high-performance flexible single-crystal rubrene OFETs on Kapton substrates with a field-effect mobility mB5 cm 2 V À 1 s À 1 that could be bent to a radius of RB6 mm without degradation. Sekitani et al 5 made an important next step toward more practical devices and demonstrated vacuumevaporated pentacene OFETs supported by polyimide substrates with mobility mB0.5 cm 2 V À 1 s À 1 that could be bent to a radius of RB3.5 mm (for devices without encapsulation) and down to 100 mm (for devices encapsulated in parylene).…”
mentioning
confidence: 99%
“…Within this effort, there are a few papers that perform tests of mechanical flexibility of organic devices and investigate the dependence of their performance on mechanical strain. For example, Briseno et al 4 developed high-performance flexible single-crystal rubrene OFETs on Kapton substrates with a field-effect mobility mB5 cm 2 V À 1 s À 1 that could be bent to a radius of RB6 mm without degradation. Sekitani et al 5 made an important next step toward more practical devices and demonstrated vacuumevaporated pentacene OFETs supported by polyimide substrates with mobility mB0.5 cm 2 V À 1 s À 1 that could be bent to a radius of RB3.5 mm (for devices without encapsulation) and down to 100 mm (for devices encapsulated in parylene).…”
mentioning
confidence: 99%
“…Previously, it has been reported that thinner crystals often lead to better OFET performances because the bulk resistance should reduce with decreasing active-layer thickness in the bottomgate, top-contact OFETs. 11 In the present study, however, all microribbons formed by ³-extended thienoacenes are thin enough (<100 nm) to minimize the effects of the resistance, so can fabricate high-performance single-crystal transistors.…”
Section: Resultsmentioning
confidence: 99%
“…Despite having synthesized a number of semiconducting organic crystals so far [309], only a few of them were successfully processed into samples fit for transport measurements and still fewer were available into few micronsized freestanding single crystals [320][321][322][323][324][325][326][327]. This clearly explains why there is a need for going into thin-film-based device development and not on large-sized wafers as in the case of Si and other inorganic semiconductors.…”
Section: Organic Single Crystalsmentioning
confidence: 99%